Y(u)=(u^-2+u^-3)(u^5-2u^2), y'=?

My attempt:

=(-2u^-3 + -3u^-4)(u^5 - 2u^2) + (5u^4-4u)(u^-2+u^-3)

=(-2u^2-4u^-1 -3u + 6u^-2) + (5u^2 +5u-4u^-1-4u^-2)

=3u^2 +2u -8u^-1+2u^-2

Where did it go wrong?

Printable View

- Oct 7th 2009, 09:24 AMhazecrazederivative problem
**Y(u)=(u^-2+u^-3)(u^5-2u^2), y'=?**

My attempt:

=(-2u^-3 + -3u^-4)(u^5 - 2u^2) + (5u^4-4u)(u^-2+u^-3)

=(-2u^2-4u^-1 -3u + 6u^-2) + (5u^2 +5u-4u^-1-4u^-2)

__=3u^2 +2u -8u^-1+2u^-2__

Where did it go wrong?

- Oct 7th 2009, 09:49 AMCalculus26
=(-2u^-3 + -3u^-4)(u^5 - 2u^2) + (5u^4-4u)(u^-2+u^-3)

=(-2u^2 + 4u^-1 -3u + 6u^-2) + (5u^2 +5u-4u^-1-4u^-2)

the u^-1 terms cancel - Oct 7th 2009, 09:57 AMhjortur